Social media in strategic management - Olivas-Lujan, Miguel R.; Bondarouk, Tanya, 1967- (Emerald, 2013)
Social media are changing the way businesses interact in technology-mediated ways with most of their stakeholders. Strategically-minded manager s, researchers and students cannot afford to ignore the new ways in which interactions with customers, employees, shareholders, and many other important constituents are taking place as a result of the widespread availability and creative use of these new technologies. Conventional wisdom is being challenged and virtual workspaces that had never been conceptualized are opening at blistering speed. This volume in the Advanced Series in Management series bridges empirical and theoretical approaches to identifying and demystify this set of emerging, exciting new family of user-gene rated content technologies. With contributions from and about a wide diverse range of countries, from emerging to established, researchers and informed practitioners will find intriguing, diverse perspectives on how the social media revolution challenging managers and management scholars. Involving disciplines as different as management, communications, information technology, personnel, finance and others, contributions in this boo k will be cited in future research projects or used in classrooms and other training settings by those more likely stay in the leading edge of this family of innovative tools.
Keywords: Strategic planning.; Social media.; elektronické knihy; electronic books